2006
DOI: 10.1007/s00228-005-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CYP2B6 alleles in malaria-endemic populations of West Africa and Papua New Guinea

Abstract: Objective-Cytochrome P450 2B6 (CYP2B6) is involved in the metabolism of artemisinin drugs, a novel series of antimalarials. Our aim was to analyze the prevalence of the most commonly observed CYP2B6 alleles in malaria-endemic populations of West Africa (WA) and Papua New Guinea (PNG).Methods-Using a post-PCR ligation detection reaction-fluorescent microsphere assay, frequencies of CYP2B6*1A, *2, *3, *4, *5, *6, *7, and *9 were determined in WA (n=166) and PNG (n=174). To compare with the results of previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 61 publications
9
79
2
Order By: Relevance
“…One explanation for these observations may center on the joint contribution of both cytochrome P450 2B6 (CYP2B6)and UGT2B7 polymorphisms. CYP2B6 is involved in the phase I metabolism of artemisinin drugs [27 for references], and CYP2B6 516G>T, associated with reduced CYP2B6 protein expression and activity [54], is the most commonly observed SNP among West Africans (50%) and Papua New Guineans (64%) [27]. We found that 33% of West Africans and 42% of Papua New Guineans carried both CYP2B6 516G>T and UGT2B7 802C>T SNPs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…One explanation for these observations may center on the joint contribution of both cytochrome P450 2B6 (CYP2B6)and UGT2B7 polymorphisms. CYP2B6 is involved in the phase I metabolism of artemisinin drugs [27 for references], and CYP2B6 516G>T, associated with reduced CYP2B6 protein expression and activity [54], is the most commonly observed SNP among West Africans (50%) and Papua New Guineans (64%) [27]. We found that 33% of West Africans and 42% of Papua New Guineans carried both CYP2B6 516G>T and UGT2B7 802C>T SNPs.…”
Section: Discussionmentioning
confidence: 92%
“…Genotyping of UGT1A9 and UGT2B7 SNPs was performed using a high throughput, post-PCR oligonucleotide ligation detection reaction-fluorescent microspheres assay (LDR-FMA) [27]. Our SNP genotyping assay is divided into 3 steps: (1) LDR, (2) FM hybridization, and (3) streptavidin-R-phycoerythrin (SA-PE) signal detection using the Bio-Plex suspension array system, which includes a fluorescence reader and the Bio-Plex Manager analytical software (Bio-Rad Laboratories, Hercules, Calif.).…”
Section: Snp Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure is described in detail elsewhere. 33 Common/conserved and allele-specific probe sequences used in this assay are listed in Supplemental Supplemental Table 2 (available online at www.ajtmh.org ). A multiplex assay was used for simultaneous detection of TLR2 and TLR9 SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…Conditions for the LDR step of this assay are described elsewhere. 33 Mean fluorescence intensity (MFI) values were used to calculate the allelic ratio for each SNP by dividing the allele-specific MFI value by the sum of the MFI values for that SNP (allele A/A + B = A n and allele B/A + B = B n ), where A and B are the 2 alleles of a SNP. To be homozygous for a particular allele, the allelic ratio must be > 0.75.…”
Section: Methodsmentioning
confidence: 99%